2021
DOI: 10.20867/tosee.06.24
|View full text |Cite
|
Sign up to set email alerts
|

Does Tourism Activity Affect Migration? Empirical Evidence From Croatia

Abstract: Purpose – Since the Census in 2011, Croatia has seen a substantial population decline. Given the high contribution of tourism to the Croatian economy, this paper empirically analyses the relationship between population migration, namely total net migration and net migration abroad, and tourism activity. Methodology – The research design of this paper is based on quantitative econometric panel data analysis using annual data for cities and municipalities in Croatia between 2002 and 2019. A oneway and two-way fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…To that extent, our research is most similar to Ivandić (2021) who showed that tourism can be seen as a generator of demographic change, especially in rural and less developed areas. However, as compared to to Ivandić (2021), to the best of our knowledge, this study is the first research to explore population changes and tourism using the 2021 Census which improves on the quality of measurement of population change.…”
Section: Discussionmentioning
confidence: 99%
“…To that extent, our research is most similar to Ivandić (2021) who showed that tourism can be seen as a generator of demographic change, especially in rural and less developed areas. However, as compared to to Ivandić (2021), to the best of our knowledge, this study is the first research to explore population changes and tourism using the 2021 Census which improves on the quality of measurement of population change.…”
Section: Discussionmentioning
confidence: 99%